Thermopower Enhancement of Bi2Te3 Films by Doping I Ions - Kim, Kwang-Chon; Baek, Seung-Hyub; Kim, Hyun Jae; Hyun, Dow-Bin; Kim, Seong Keun; Kim, Jin-Sang (SPRINGER, 2014)
The thermoelectric properties of I-doped Bi2Te3 films grown by metal-organic chemical vapor deposition have been studied. I-doped epitaxial (00l) Bi2Te3 films were successfully grown on 4A degrees tilted GaAs (001) substrates at 360 A degrees C. I concentration in the Bi2Te3 films was easily controlled by the variation in a flow rate of H-2 carrier gas for the delivery of an isopropyliodide precursor. As I ions in the as-grown Bi2Te3 films were not fully activated, they did not influence the carrier concentration and thermoelectric properties. However, a post-annealing process at 400 A degrees C activated I ions as a donor, accompanied with an increase in the carrier concentration. Interestingly, the I-doped Bi2Te3 films after the post-annealing process also exhibited enhancement of the Seebeck coefficient at the same electron concentration compared to un-doped Bi2Te3 films. Through doping I ions into Bi2Te3, the thermopower was also enhanced in Bi2Te3, and a high power factor of 5 x 10(-3) W K-2 m(-1) was achieved.